STRUCTURE OF IRIDIUM(III) HYDRATION BASED ON AB INITIO QUANTUM MECHANICAL CHARGE FIELD MOLECULAR DYNAMICS SIMULATIONS - Ponco Iswanto; Ria Armunanto; Harno D. Pranowo (Universitas Gadjah Mada, 2010)
Structural properties of Iridium(III) hydration have been studied based on an ab initio Quantum Mechanical Charge Field (QMCF) Molecular Dynamics (MD) Simulations. The most chemical-relevant region was treated by ab initio calculation at Hartree-Fock level. For the remaining region was calculated by Molecular Mechanics method. LANL2DZ ECP and DZP Dunning basis sets were applied to Ir3+ ion and water, respectively. The average distance of Ir-O in the first hydration shell is 2.03 Å. The QMCF MD Simulation can detect only one complex structure with coordination number of 6 in the first hydration shell. Bond angle analysis shows that Ir3+ ion hydration in the first hydration shell has octahedral structure.